ANALISIS KETERCAPAIAN INDIKATOR STANDAR PROSES PADA MA ADDZURIYATUS SHOLIHIN - Sinta Nurhayati; Leni Redha; Lastia Laksana (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThis article aims to determine the standard of the research process at MAAdzuriyatus Solihin ciparay Bandung. This research is a qualitative research bycollecting data in the form of observation, interviews and documentation. The results ofthis study indicate that the achievement of process standards at MA Adzuriyatus SolihinCiparay Bandung is 91.42% when compared to the entire maximum score that shouldbe achieved in the standard process. This study recommends in-depth. indicators thathave not been achieved optimally, especially school indicators carry out the learningprocess with a maximum of 36 students in the study group and the teacher conducts goodclassroom management with 12 criteria. According to the author, the principal mustconduct an evaluation and supervision of the way to teach in the class, also conducttraining for teachers who have not been able to achieve standard process indicators.Because in learning the class of educators plays an important role in the learningprocess. This is intended to improve the quality of education and satisfaction ofcommunity expectations.Keynotes: process standards, educators, students